Gates and Entrances in Ezekiel 40–48: The Social Utopia of the Temple Vision - Rhyder, Julia (Vetus Testamentum, 2023)
The temple vision of Ezek 40–48 devotes considerable attention to measuring and describing the various gates and entrances of the temple compound. Previous studies have tended to focus on the defensive function of the gates. However, these structures not only bar entry but also facilitate access to the temple under certain ritualized conditions. Offering a close reading of the references to the gates in Ezek 40–48, in which particular roles and activities are associated with specific entrances, this article shows how these architectural features of the temple map a differential system in which social hierarchies are organized according to the level, direction, and timing of access ascribed to different groups and individuals within the temple compound. The article concludes by exploring the significance of the gates for how we understand the literary genre of the temple vision of Ezek 40–48, and in particular its nature as a social utopia.